2013
DOI: 10.1152/ajpregu.00162.2013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abnormally high leptin levels during pregnancy on metabolic phenotypes in progeny mice

Abstract: Makarova EN, Chepeleva EV, Panchenko PE, Bazhan NM. Influence of abnormally high leptin levels during pregnancy on metabolic phenotypes in progeny mice. Am J Physiol Regul Integr Comp Physiol 305: R1268 -R1280, 2013. First published October 2, 2013; doi:10.1152/ajpregu.00162.2013.-Maternal obesity increases the risk of obesity in offspring, and obesity is accompanied by an increase in blood leptin levels. The "yellow" mutation at the mouse agouti locus (A y ) increases blood leptin levels in C57BL preobese pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 54 publications
(65 reference statements)
4
20
0
4
Order By: Relevance
“…To induce obesity, mice were fed during 10 weeks with mixed diet, which consisted of standard laboratory chow supplemented with sweet cookies, sunflower seeds and lard -sweet and fat diet. Previously we have shown that this sweet and fat diet rapidly induced obesity in C57Bl mice (Makarova et al, 2013). Mice of control group consumed for 10 weeks standard laboratory chow.…”
Section: Methodsmentioning
confidence: 99%
“…To induce obesity, mice were fed during 10 weeks with mixed diet, which consisted of standard laboratory chow supplemented with sweet cookies, sunflower seeds and lard -sweet and fat diet. Previously we have shown that this sweet and fat diet rapidly induced obesity in C57Bl mice (Makarova et al, 2013). Mice of control group consumed for 10 weeks standard laboratory chow.…”
Section: Methodsmentioning
confidence: 99%
“…On GD12, the females received subcutaneous injections of recombinant murine leptin (4.0 µgÁg À1 BW) dissolved in saline to a final concentration of 500 µgÁmL À1 or were injected with saline (control) at 9 h 00 min. According to our previous research, leptin administered at this dose to mice in late pregnancy did not affect the offspring viability but this administration influenced the offspring phenotype [5]. The leptin-and saline-administered mice were divided into three experimental groups.…”
Section: Animalsmentioning
confidence: 99%
“…These offspring had decreased weight gain after weaning, were not hyperphagic, and gained less weight after fasting , though they were less responsive to exogenous leptin administration (Makarova et al, 2013). The same study found that offspring from wildtype mouse dams injected with leptin at gestational day 17 had lower body weight, and male offspring had reduced food intake and diet induced obesity (Makarova et al, 2013). In contrast, a previous study from our lab showed that female offspring from mouse dams that were food-restricted and administered leptin during the first half of pregnancy became obese when given a high fat diet .…”
Section: Hyperleptinemia Modelsmentioning
confidence: 93%
“…Also, both male and female offspring from leptin treated dams had increased energy expenditure when on a high fat diet (Stocker et al, 2007). There is some evidence that mouse dams heterozygous for a mutation at the agouti locus have high leptin without other metabolic alterations at a young age, and their offspring were also resistant to obesity (Makarova et al, 2013). These offspring had decreased weight gain after weaning, were not hyperphagic, and gained less weight after fasting , though they were less responsive to exogenous leptin administration (Makarova et al, 2013).…”
Section: Hyperleptinemia Modelsmentioning
confidence: 99%
See 1 more Smart Citation